GLOBALISASI DAN IMPAK SOSIOBUDAYA - Aishah Haji Mohamed (Universitas Andalas, 2017)
Globalization, the ongoing process of greater interdependence among countries and their citizens, is complex and multifaceted. Many of the problems that the critics of globalization point to are real. This article on the socio-cultural impact of globalization on the semi-urban populations uses data collected in three districts in Selangor (Sepang, Kuala Selangor and Kuala Langat), Malaysia using survey and in depth interviews method. The socio-cultural impact of globalization on the semi-urban populations of Selangor can be seen from several angles. Among other things are the changes in interpersonal relationship due to changes in occupations, places of works, places of residence and different work schedules. Thus a new kind of relationship evolved i.e. between different categories of workers and the management. This creates a totally new environment whereby the management determined certain aspects of the life of workers such as pay rise and work schedules. Their life styles are also different. With the improved economic condition more job opportunities are available for foreign workers and women. The children are now being looked after by maids or the so called transit houses which are not based on family relationship. The influx of foreign workers also expose the local populations to various infectious diseases such as tuberculosis, malaria (which had been eradicated in the country long time ago), SARS and H1N1.